Biochemical changes in tissues of albino rats following subchronic exposure to crude oil - Nwaogu LA; CU, Igwe; CO, Ujowundu; U, Arukwe; CE, Ihejirika; AV, Iweke (Journal of Research in Biology, 2011)
Biochemical changes in the tissues of thirty-six albino rats (Rattus rattus) following subchronic exposure to 1.25% , 2.50% and 5% of crude oil polluted feed was investigated. There were age and sex matched with another twelve albino rats fed without crude oil. The exposure period lasted for thirty days. The concentrations of serum albumin, cholesterol and glucose, liver total protein, ascorbic acid and reduced glutathione (GSH) as well as the activities of alanine amino transferase (ALT), aspartate amino transferase (AST), alkaline phosphatase (ALP) and catalase (CAT) from the rats were determined using standard methods. The results indicate that there were no significant (P>0.05) changes in these parameters from the rats fed with 1.25% and 2.50% crude oil mixed feed when compared with the control. However, significant (P<0.05) reductions were observed in glucose, ascorbic acid and GSH concentrations as well as in catalase activity, with a concomitant significant (P>0.05) increases in serum ALT, AST and ALP activities in the rats fed 5% crude oil polluted feed, in comparison with the control. The results indicate that crude oil ingestion at levels of up to 5% may have serious adverse effect on animal tissues